FERMENTED BLOOD MEAL USE FOR TIGER GROUPER, Epinephelus fuscoguttatus GROW-OUT DIET - Usman Usman; Kamaruddin Kamaruddin; Neltje Nobertine Palinggi; Rachmansyah Rachmansyah; Taufik Ahmad (Indonesian Aquaculture Journal, 2007)
The experiment aimed to evaluate the optimal level of fermented blood meal used in grow-out diets for tiger grouper, as an alternative protein source to fish meal. Juvenile tiger grouper, initial weight 31.1 ± 2.1 g, were stocked into 1 m x 1 m x 2 m floating net cages at 20 fish cage-1. The treatment applied was isoprotein and isocaloric diets formulated to contain fermented blood meal (FBM) of 0%, 7.5%, 15.0%, 22.5%, and 30.0% replacement of fish meal protein. The diets were fed to the fish twice a day to satiation for 20 weeks. Based on the Tukey test, the fish fed 0%–15.0% FBM demonstrated similar performance (P>0.05) to those fed the control diet (FBM0) in terms of specific growth rate, weight gain, and feed and protein efficiency. Specific growth rate, weight gain, feed efficiency and protein efficiency of the fish fed 22.5%–30.5% FBM were significantly lower (P<0.05) than those of the fish fed control diet (FBM0). However, there was a significant culvilinier decliner in overall fish performance with increasing inclusion of FPM and most notable for weight gain, feed efficiency and feed consumption. Based on regression analysis, the asymptote where fish growth deteriorates as a function of FBM inclusion was determined to be 8.9%. Tiger grouper diets incorporating up to 9% FBM as fish meal replacement had no adverse affects on fish growth and survival.